[18F]FDG-PET/CT in Staphylococcus aureus bacteremia: a systematic review - D. T. P. Buis; E. Sieswerda; I. J. E. Kouijzer; W. Y. Huynh; G. L. Burchell; M. A. H. Berrevoets; J. M. Prins; K. C. E. Sigaloff (BMC Infectious Diseases, 2022)
Abstract Objectives [18F]FDG-PET/CT is used for diagnosing metastatic infections in Staphylococcus aureus bacteremia (SAB) and guidance of antibiotic treatment. The impact of [18F]FDG-PET/CT on outcomes remains to be determined. The aim of this systematic review was to summarize the effects of [18F]FDG-PET/CT on all-cause mortality and new diagnostic findingsin SAB. Methods We systematically searched PubMed, EMBASE.com, Web of Science, and Wiley’s Cochrane library from inception to 29 January 2021. Eligible studies were randomized controlled trials, clinically controlled trials, prospective and retrospective cohort studies, and case–control studies investigating the effects of [18F]FDG-PET/CT in hospitalized adult patients with SAB. We excluded studies lacking a control group without [18F]FDG-PET/CT. Risk of bias was assessed using the ROBINS-I tool and certainty of evidence using the GRADE approach by two independent reviewers. Results We identified 1956 studies, of which five were included in our qualitative synthesis, including a total of 880 SAB patients. All studies were non-randomized and at moderate or serious risk of bias. Four studies, including a total of 804 patients, reported lower mortality in SAB patients that underwent [18F]FDG-PET/CT. One study including 102 patients reported more detected metastatic foci in the participants in whom [18F]FDG-PET/CT was performed. Discussion We found low certainty of evidence that [18F]FDG-PET/CT reduces mortality in patients with SAB. This effect is possibly explained by a higher frequency of findings guiding optimal antibiotic treatment and source control interventions.